Antibiotic Susceptibility and Resistance Patterns in Urine Cultures - A Single Center Experience - Naureen Chaudri, Naureen Chaudri (Journal of Rawalpindi Medical College, 2020)
Introduction: Antimicrobial resistance is a threatening global medical challenge. Its prevalence is on the rise, more so in developing countries like Pakistan. It is pivotal to know and follow the local drug sensitivity and resistance pattern for effective empirical treatment of urinary tract infections. Objectives: To evaluate antibiotic susceptibility and resistant patterns of different urinary pathogens in cultures among patients presented in a tertiary care hospital. Materials and Methods: A Descriptive Cross-sectional study was carried out at the Department of Nephrology and Microbiology Holy Family Hospital, Rawalpindi Medical University from January 2018 to July 2018. All the samples from patients suspected to be suffering from UTI that were ordered a urine culture by attending doctors were recruited for the study and were sent to the central pathology laboratory of the hospital. All urine cultures performed in HFH were recruited for the study including both inpatient and outpatient departments. Data were collected in a structured performa and were entered and analyzed in SPSS version 21.0. Results: 402/1216 (33.0 %) urine samples had positive bacterial growths. Females accounted for the majority of 61.6% of cases. E.coli was the most common isolate 42.7%, followed by Klebsiella spp. 17.5%. E.coli exhibited high antimicrobial resistance, with the least resistance to fosfomycin 13.6%. E.coli, Klebsiella spp. and pseudomonas showed significant coresistance to Ceftazidime and ciprofloxacin. Conclusion: Emergence of high AMR in a developing country like Pakistan can have grave clinical and economic implications. It adversely impacts all aspects of patient care. It limits therapeutic options and leads to treatment failure.